Anomalous origin of the fetal pulmonary artery - Huang, Qiong; Ling, Wen; Wu, Qiumei; Guo, Shan; Dang, Tingting; Ma, Hong; Huang, Biying; Chen, Chunxia; Liu, Min; Qiu, Xiuqing; Weng, Zongjie (Frontiers in Pediatrics, 2023)
Objectives: To investigate the value of prenatal ultrasound in diagnosing the fetal anomalous origin of the pulmonary artery. Methods: Abnormal origin of the fetal pulmonary artery from January 2014 to January 2023 was retrospectively analyzed. Compared with the anatomical cast specimen after induction or postnatal imaging and surgical result to characterize the fetal anomalous origin of the pulmonary artery and demonstrate the reasons for missed diagnosis and misdiagnosis. Results: Twenty-six cases of fetal pulmonary artery origin abnormalities included thirteen cases of pulmonary artery sling (PAS), eight cases of anomalous origin of the unilateral pulmonary artery (AOPA), and five cases of unilateral absence of the pulmonary artery (UAPA). There were seventeen cases of pathological anatomy and casting after induction, and nine cases were confirmed by postnatal imaging and surgery. Conclusions: Prenatal ultrasound has crucial diagnostic value for fetal anomalous origin of the pulmonary artery, and one side of the pulmonary artery in the section of pulmonary artery bifurcation which has never been shown is an essential clue for diagnosing pulmonary artery origin abnormalities, in addition, the location of the abnormal origin of the pulmonary artery on the affected side should be further found, and attention should be paid to whether other intracardiac malformations complicate the fetus.